Betel nut use and hyperglycemia - Edward Nabrinsky; Badar Hasan; Talal Asif; Rebecca R. Pauly (Marshall Journal of Medicine, 2017)
Betel nut chewing previously has not been common in North America, yet it is the fourth major source of addiction and abuse worldwide. Approximately 700 million individuals, or 10 % of the global population, chew beetle nut on regular basis. It is important for patient safety and improved quality to recognize its use in uncontrolled diabetes. Our case is of a 49 year-old Burmese female with PMH of DM2, HTN, and benign paroxysmal positional vertigo (BPPV) who presented with a complaint of dizziness. Patient denied alcohol or tobacco use, but reported a 20-year history of betel nut chewing (4-5 times/day). Physical exam showed oral mucosa was dry with poor dentition along with eroded enamel and gums. Point-of-care glucose was extremely elevated at 522 mg/dL with HbA1c of 10.8%. Dix-Hallpike maneuver was negative and CTA of the head and neck was unremarkable. Neurology was also consulted regarding her dizziness, and MRI head demonstrated no acute infarct or hemorrhage. Throughout admission, patient’s point of care glucose fluctuated between 91 and 316 (mg/dL), with several daily spikes. Her dizziness improved by day 2 of hospitalization. At the time of discharge, her glucose was controlled on 50 units of glargine at nighttime along with 8 units of insulin at meals. After a negative initial workup for occult causes of dizziness, it was concluded that her 20-year history of betel nut chewing contributed to dizziness and hyperglycemia. Multiple studies show high risk of diabetes, increased likelihood of coronary artery disease and all-cause mortality in betel nut users. Specifically, one study in Taiwan demonstrated increasing incidence ratios of type II diabetes with increasing age.